Pelatihan Sistem Informasi Desa (SID) Dan Website Desa Untuk Peningkatan Pelayanan di Desa Moyot Melalui Program Kompetisi Kampus Merdeka(PKKM) - Bahtiar, Hariman; Sadali, Muhamad; Sudianto, Aris; Nur, Amri Muliawan; Firdaus, Ahmad (Universitas Hamzanwadi, 2023)
At this time, technological developments have developed very rapidly and quickly, bringing about very big changes because they make the information obtained available quickly, easily, accurately and not limited by place and time. A village is a community unit that has a structure based on special characteristics. Village government contains participation, diversity, genuine autonomy, democratization and community empowerment. Moyot Village is a village in Sakra subdistrict, East Lombok Regency, West Nusa Tenggara Province. From the results of the analysis it can be concluded that in Moyot Village, Sakra District, several weaknesses were found in village services or village administration. With the existence of village technology development programs such as Village Information Systems and Village Websites, it is hoped that it will make it easier for village officials to carry out public services such as conveying data information online. transparency and can be known by the community without having to go to the village office to ask what is in the village and what will be done in the village, such as APBDes funds and so on.